Delivered from the Temptation of Smoking: An Examination of Religion and Health Behaviors of New US Immigrants - Cartwright, Kate (Journal of religion and health, 2021)
This study aims to contribute to the literature on smoking, religion, and health, by analyzing the associations between smoking and health of a sample of US immigrants, who represent many religions, ethnicities, and cultural backgrounds. Immigrants to the USA have better health outcomes than their native-born peers. This paper asserts that the pattern of smoking, influenced by immigrants’ religion and religiosity, is key to understanding this phenomenon. This study investigates the relationship between religion and health of new legal immigrants to the USA by analyzing the New Immigrant Survey. The findings suggest that there is a protective relationship between immigrant religion and smoking patterns, both in likelihood of having ever smoked and in quitting smoking.